1999
DOI: 10.1590/s0103-90161999000500008
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento da parte aérea de cana crua e queimada

Abstract: nd years of second ratoon cane crop, by means of adapted curves. The research was performed in Morro Agudo, SP, Brazil from July 1995 to July 1997. The cultivar was the SP 70 -1143. As growth indicators the following biometric indexes were used: number of tillers, number of leaves, dry matter of stalks, and leaves and leaf area index (LAI). For each treatment, 4 areas were used, each one being considered a replication. Polynomial regression and non-linear regression were used to adjust the data to the growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
2
4
0
4
Order By: Relevance
“…The 75% level of ETc had the fastest growth, growing 1.96 cm day -1 , and the 150% level had the slowest, with growth of only 1.81 cm day -1 . This same pattern was observed by Alvarez and Castro (1999) and INMAN-BAMBER et al (2002), who reported that culm elongation coincided with the period in which the LA was greatest.…”
Section: Resultssupporting
confidence: 85%
“…The 75% level of ETc had the fastest growth, growing 1.96 cm day -1 , and the 150% level had the slowest, with growth of only 1.81 cm day -1 . This same pattern was observed by Alvarez and Castro (1999) and INMAN-BAMBER et al (2002), who reported that culm elongation coincided with the period in which the LA was greatest.…”
Section: Resultssupporting
confidence: 85%
“…The number of stalks averaged 16 stalks per linear meter, with an average length of 1.57 m (Figures 7A and 7C) and an average diameter of 2.27 cm ( Figure 7E). Similar results for the number of stalks were found by Alvarez and Castro (1999), where the tillering was similar for the production systems, raw cane and burnt cane, in the first year of ratoon cane, with an average of 21 tillers per meter for raw cane and 20 for burnt cane.…”
Section: Resultssupporting
confidence: 82%
“…Stalk diameter over the course of plant development showed a reduction in relation to the start of development Alvarez and Castro (1999) at 60 DAP. also found a reduction in stalk diameter in cane harvested raw in the first and second years.…”
Section: Resultsmentioning
confidence: 98%
“…Para esse estudo, têm sido utilizados vários modelos lineares e não-lineares para descrever crescimento ao longo do tempo (ALVAREZ & CASTRO, 1999;URCHEI et al, 2000;HERNÁNDEZ et al, 2007 Ciência Rural, v.39, n.5, ago, 2009. em relação aos modelos lineares, os quais podem auxiliar o pesquisador no processo de tomada de decisão por apresentarem parâmetros com interpretação biológica. Dentre essas funções não-lineares, pode-se citar os modelos de: Brody ou Monomolecular (BRODY, 1945), Gompertz (WINSOR, 1932), Logístico (NELDER, 1961) e von Bertalanffy (von BERTALANFFY, 1957).…”
Section: Introductionunclassified